Polymer electrolyte material photo-anode and preparation method and application thereof
Patent Information
- Application Number
- CN202510284836.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-03-11
AI Technical Summary
[0005]本发明的目的在于提供一种聚合物电解质材料光电阳极及其制备方法和应用,用以解决现有的光阳极结构不稳定导致的光电催化性能差的技术问题
本发明公开了一种聚合物电解质材料光电阳极的制备方法,通过对聚合物进行结构设计,引入了嵌段膦酸基团片段,嵌段膦酸基团片段相较于传统的单个膦酸集团能有效减缓了催化剂的解吸附过程,有效延长了催化剂在光电阳极上的停留时间,提高了光电催化的稳定性;同时引入的长烷基链的疏水结构,长烷基链的疏水结构让解吸附的催化剂靠近半导体界面,使其处于吸附-解吸附的动态平衡,进一步延长了催化剂在光电阳极上的停留时间,提高了光电催化的稳定性;同时在制备过程中,通过长烷基链间的非分子间相互作用,采用自组装策略简化了传统复杂合成过程,同时通过精准调控催化剂和光敏剂的组成,进一步优化了聚合物电解质材料光电阳极的光电催化性能。这种精准的组成调控使得光阳极在光电催化过程中能够更高效地利用光能,提高了光生电子和空穴的分离效率提高了催化稳定性。
Smart Images

Figure CN119980346B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photoelectrocatalytic water splitting and oxygen evolution materials technology, specifically relating to a polymer electrolyte material photoanode, its preparation method, and its application. Background Technology
[0002] Artificial photosynthesis, as a cutting-edge technology simulating the natural photosynthetic process, aims to efficiently capture and utilize solar energy, converting it into directly storeable and transportable solar fuels. Driven by this ambitious goal, fuel-sensitized photoelectrochemical cells (DSPECs) have emerged as an important strategy in exploring pathways for artificial photosynthesis. DSPEC technology cleverly utilizes photosensitizers as the energy conversion medium, directly converting captured solar energy into chemical energy. This mechanism not only revolutionizes energy conversion methods but also provides new ideas for the development of sustainable energy. The dye-sensitized photoanode, a key component of the DSPEC system, features an ingenious structural design, typically consisting of a conductive glass substrate as a support, semiconductor materials as a bridge for electron transport, and carefully selected photosensitizers and water oxidation catalysts. This combination endows the photoanode with a broad spectral absorption capability. Compared to traditional inorganic semiconductor photoanodes, dye-sensitized photoanodes exhibit a superior spectral response range and a slower carrier recombination rate, resulting in a significant improvement in energy conversion efficiency and attracting widespread attention from the energy materials science community. However, despite the numerous theoretical advantages of dye-sensitized photoanodes, they face significant challenges in practical applications. In particular, the adsorption and desorption processes of photosensitizers and catalysts on the photoanode surface often become key factors limiting the long-term stability of the device and the maintenance of photocurrent density. The instability of these surface dynamic processes leads to a rapid decline in photoanode performance and a sharp decrease in photocurrent density over time, severely hindering the commercialization of DSPEC technology. Therefore, optimizing the interfacial interaction between photosensitizers and catalysts to improve device stability has become a core problem urgently needing to be solved in the current research field of dye-sensitized photoelectrochemical cells.
[0003] To improve the stability of photoanodes, researchers are constantly exploring new strategies. Two common methods are introducing long hydrophobic alkyl chains and using atomic layer deposition (ALD). Introducing long hydrophobic alkyl chains aims to enhance the stability of the photosensitizer and reduce its desorption on the photoanode surface; while ALD technology encapsulates the photosensitizer by depositing oxides or polymer compounds, thus protecting it from environmental impacts. However, these methods face many challenges in practical applications, such as complex chemical synthesis steps, high equipment costs, and potential reductions in electron transfer rates. These factors constrain the realization of high-efficiency DSPEC systems. Therefore, there is an urgent need to design novel electrode structures and assembly strategies to significantly improve the stability of photoanodes without sacrificing DSPEC efficiency. This has significant theoretical and practical value for optimizing the structure of dye-sensitized photoanodes and further improving the performance of photoelectrocatalytic water oxidation.
[0004] Existing literature reports that phosphonic acid groups exhibit strong binding affinity and high electron injection efficiency to metal oxides. However, molecularly modified electrodes containing only a single phosphonic acid group typically exhibit poor stability, especially at pH values above 6. Summary of the Invention
[0005] The purpose of this invention is to provide a polymer electrolyte material photoanode, its preparation method, and its application, in order to solve the technical problem of poor photoelectrocatalytic performance caused by the instability of existing photoanode structures.
[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a polymer electrolyte material photoanode, comprising the following steps: The copolymer was subjected to a hydrolysis reaction to obtain the hydrolyzed polymer; the hydrolyzed polymer and the catalyst were then subjected to a coordination reaction to obtain the polymer grafted with the catalyst. The polymer grafted with the catalyst was dissolved in a solvent to obtain a mixed solution; After coating a core-shell structured electrode onto a substrate, the electrode is immersed in a mixed solution to obtain an assembled electrode with a surface-anchored catalyst. By placing the assembled electrode with the surface-anchored catalyst in a photosensitizer solution, a polymer electrolyte material photoanode is obtained.
[0007] Furthermore, the chemical structural formula of the hydrolyzed polymer is shown below: ; Where: R is C 10 H 21 Long alkyl chain.
[0008] Furthermore, the copolymer is prepared by the following method: 2-Methylpropion-2-enoic acid pyridin-4-yl ester, {[(2-methyl-1-oxylidenepropion-2-enyl)oxy]methyl}phosphonate diethyl ester and 2-methylpropion-2-enoic acid decyl ester were dissolved in THF, subjected to a freeze-pump-thaw cycle under a nitrogen atmosphere, and then heated to reflux to obtain a mixture; The mixture was cooled and concentrated to obtain a crude product; a hexane copolymer was added to the crude product to react and obtain a copolymer. The ratio of pyridin-4-yl 2-methylpropionic acid, diethyl phosphonate {[(2-methyl-1-oxoylidene-2-enyl)oxy]methyl}phosphonate, decyl 2-methylpropionic acid, and THF is (40~50) mg : (10~30) mg : (30~40) mg : (7~15) mL; The freezing-pump-thawing cycle is repeated three times; the heating and reflux process involves heating to 70-90 °C and refluxing for 36-48 h. The ratio of the crude product to the hexane copolymer is (1~2) mL: (50~80) mL.
[0009] Furthermore, the specific steps for hydrolyzing the polymer are as follows: The copolymer was dissolved in DCM, and then an excess of trimethylbromosilane was added under N2 atmosphere to react and obtain a reaction mixture. The reaction mixture was heated and stirred, and then an excess of methanol was added to obtain the precipitated copolymer. The precipitated copolymer was washed and dried sequentially to obtain the hydrolyzed polymer. The ratio of the copolymer to DCM is (30~50) mg : (2~20) mL; The ratio of the copolymer, trimethylbromosilane, and methanol is (30~50) mg: (1-3) mL: (1-3) mL; The temperature at which excess trimethylbromosilane is added is 0 °C; The heating process involves heating from 0°C to room temperature; the stirring time is 12 hours.
[0010] Furthermore, the catalyst is prepared by the following method: 2,2'-bipyridine-6,6'-dicarboxylic acid, Ru(DMSO)4Cl2, and NEt3 were added to methanol and refluxed under N2 atmosphere to obtain Ru(bda)(DMSO)2. After mixing 4-pyridine, Ru(bda)(DMSO)2 with methanol, the mixture was degassed and refluxed in a N2 atmosphere, and then eluted and purified to obtain the Ru(bda)(DMSO)(4-picoline) catalyst. The ratio of 2,2'-bipyridine-6,6'-dicarboxylic acid, Ru(DMSO)4Cl2, NEt3, and methanol was 488 mg: 968 mg: 1.6 mL: 80 mL; the mixture was refluxed under a N2 atmosphere to obtain Ru(bda)(DMSO)2, and the reflux time was 4 h. The ratio of 4-pyridine, Ru(bda)(DMSO)2 and methanol is 93 mg: 500 mg: 40 mL; The reflux time for obtaining the Ru(bda)(DMSO)(4-picoline) catalyst was 1 h. The eluent used for elution is a mixture of dichloromethane and methanol in a volume ratio of 1:1.
[0011] Furthermore, the specific steps for the coordination reaction between the hydrolyzed polymer and the catalyst are as follows: The hydrolyzed polymer and catalyst were stoichiometrically combined in methanol and a coordination reaction was carried out under N2 atmosphere to obtain a polymer grafted with the catalyst. The ratio of the hydrolyzed polymer to the catalyst is (10~20) mg: (32~50) mg; The ratio of polymer to solvent in the grafted catalyst is (5~10) mg: (5~8) mL; The solvent is methanol or acetonitrile.
[0012] Furthermore, the specific steps for the coordination reaction between the hydrolyzed polymer and the catalyst are as follows: The hydrolyzed polymer and catalyst were stoichiometrically combined in methanol and a coordination reaction was carried out under N2 atmosphere to obtain a polymer grafted with the catalyst. The ratio of the hydrolyzed polymer to the catalyst is (10~20) mg: (32~50) mg; The ratio of polymer to solvent in the grafted catalyst is (5~10) mg: (5~8) mL; The solvent is methanol or acetonitrile.
[0013] The present invention also discloses a polymer electrolyte material photoanode prepared by the above preparation method.
[0014] This invention also discloses the application of the above-mentioned polymer electrolyte material photoanode in photoelectrocatalysis, including the following steps: Using photoelectrocatalysis as the working electrode, a three-electrode system was constructed. Electrocatalytic reactions were carried out in the electrolyte solution of the three-electrode system to release oxygen.
[0015] Furthermore, the electrolyte solution is a neutral solution; the concentration of the electrolyte solution is 0.5 M.
[0016] Furthermore, the neutral solution is prepared by adding 0.5 M sodium perchlorate to a phosphate buffer solution.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a polymer electrolyte material photoanode. By structurally designing the polymer, block phosphonic acid groups are introduced. Compared to traditional single phosphonic acid groups, these groups effectively slow down the catalyst desorption process, extending the catalyst's residence time on the photoanode and improving photoelectrocatalytic stability. Simultaneously, the introduction of long alkyl chain hydrophobic structures allows the desorbed catalyst to approach the semiconductor interface, maintaining a dynamic equilibrium between adsorption and desorption, further extending the catalyst's residence time on the photoanode and improving photoelectrocatalytic stability. Furthermore, during the preparation process, a self-assembly strategy is employed through non-intermolecular interactions between the long alkyl chains, simplifying the traditional complex synthesis process. Precise control of the catalyst and photosensitizer composition further optimizes the photoelectrocatalytic performance of the polymer electrolyte material photoanode. This precise compositional control enables the photoanode to utilize light energy more efficiently during photoelectrocatalysis, improving the separation efficiency of photogenerated electrons and holes and enhancing catalytic stability.
[0018] Furthermore, the preparation method of the present invention has the advantages of controllable process, simple process, and low cost, making it suitable for large-scale production and conducive to industrial application.
[0019] The present invention also discloses a polymer electrolyte material photoanode prepared by the above preparation method. This photoanode has multiple advantages such as stable structure and good oxygen evolution effect. It not only optimizes the structure of dye-sensitized photoanode, but also significantly improves its photoelectrocatalytic water oxidation performance, which is of great significance for promoting the development of photoelectrocatalysis technology. Attached Figure Description
[0020] Figure 1 The 1H NMR spectra of the Ru(bda)(DMSO)(4-picoline) catalyst and RuPSL photosensitizer prepared in Example 1 of this invention are shown below. Among them: a-Ru(bda)(DMSO)(4-picoline) catalyst; b-RuPSL photosensitizer; Figure 2 The infrared spectrum of the copolymer prepared in Example 1 of this invention; Figure 3The image shows the ultraviolet absorption spectrum of the photoanode of the polymer electrolyte material photoanode prepared in Example 1 of this invention. Figure 4 The graph shows the photoelectrocatalytic performance of the polymer electrolyte material photoanode prepared in Example 1 of this invention. Figure 5 The image shows a long-term photocurrent test diagram of the electrocatalytic performance of the polymer electrolyte material photoanode prepared in Example 1 of this invention and the amount of oxygen evolved in the photoelectrocatalytic water splitting reaction. Where: a-long-term photocurrent test graph; b-oxygen evolution amount in photoelectrocatalytic water splitting reaction; Figure 6 The graph shows the photoelectric conversion efficiency of the polymer electrolyte material photoanode prepared in Example 1 of this invention. Detailed Implementation
[0021] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0023] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0024] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0025] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0026] This invention provides a polymer electrolyte material photoanode. By designing a polymer, a copolymer scaffold containing pyridine groups, phosphonic acid groups, and long alkyl chains is proposed. Subsequently, a catalyst is grafted onto this polymer through coordination, adsorbing it onto the surface of a metal oxide. Then, a photosensitizer is connected through non-intermolecular interactions between the long alkyl chains. This polymer electrolyte material photoanode exhibits structural stability, good photoelectrocatalytic performance, and excellent oxygen evolution efficiency in the photoelectrocatalytic splitting of water and oxygen.
[0027] The chemical structural formula of the polymer obtained by the above design is shown in formula (I): (I) Among them, R Group is C 10 H 21 Long alkyl chains; This invention also discloses a method for preparing the above-mentioned polymer electrolyte material photoanode, comprising the following steps: S1: The monomers pyridin-4-yl 2-methylprop-2-enoate, diethyl phosphonate {[(2-methyl-1-oxoylide-2-enyl)oxy]methyl}phosphonate and decyl 2-methylprop-2-enoate were obtained by free radical polymerization to obtain a copolymer; S2: The copolymer obtained in step S1 is subjected to hydrolysis under the action of trimethylbromosilane to obtain the hydrolyzed polymer; S3: The hydrolyzed polymer obtained in step S2 is subjected to a coordination reaction with the catalyst (Ru(bda)(DMSO)(4-picoline)) to obtain the polymer grafted with the catalyst; S4: Dissolve the obtained polymer of the grafted catalyst in methanol to obtain a mixed solution. Coat a core-shell structured electrode on conductive glass FTO and place it in the mixed solution to obtain an assembled electrode with surface-anchored catalyst. S5: The assembled electrode with the surface-anchored catalyst is placed in a photosensitizer (RuPSL) solution to obtain a polymer electrolyte material photoanode.
[0028] Preferably, in S1, the preparation of the copolymer includes the following steps: 2-Methylpropion-2-enoic acid pyridin-4-yl ester, {[(2-methyl-1-oxoylidenepropion-2-enyl)oxy]methyl}phosphonate diethyl ester and 2-methylpropion-2-enoic acid decyl ester were dissolved in anhydrous and oxygen-free THF, and subjected to three freeze-pump-thaw cycles under a nitrogen atmosphere. Finally, O2 was removed from the solvent, and the mixture was heated to 70 °C and refluxed for 48 h. Stop heating and allow the mixture to cool to room temperature. Concentrate the crude product in tetrahydrofuran to 1 mL and then add 50 mL of n-hexane to precipitate the copolymer. The solid was filtered and washed with n-hexane to remove unreacted monomers; The product was separated and dried under high vacuum to obtain a white solid (polymer).
[0029] Preferably, the hydrolysis reaction of the copolymer includes the following steps: The copolymer was dissolved in 2 mL of dry DCM, and excess trimethylbromosilane was added at 0 °C under N2 atmosphere to obtain the reaction mixture. The reaction mixture was heated from 0 °C to room temperature and stirred overnight, and then the copolymer was precipitated after the addition of excess methanol; The solid was filtered and washed with methanol, the product was separated and dried under high vacuum to obtain a pale yellow solid (polymer).
[0030] Preferably, in S3, the catalyst (Ru(bda)(DMSO)(4-picoline)) is prepared by the following method: 488 mg of 2,2'-bipyridine-6,6'-dicarboxylic acid, 968 mg of Ru(DMSO)4Cl2, and 1.6 mL of NEt3 were added to 80 mL of methanol and refluxed with N2 for 4 h to obtain Ru(bda)(DMSO)2. The mixture of 4-pyridine (93 mg) and Ru(bda)(DMSO)2 (500 mg) in methanol (40 mL) was degassed with N2 and refluxed for 1 h; The product was obtained by silica gel column chromatography using dichloromethane-methanol (1:1, v:v) as the eluent.
[0031] Preferably, in step S3, the coordination reaction between the hydrolyzed polymer and the catalyst (Ru(bda)(DMSO)(4-picoline)) is as follows: The corresponding dried hydrolyzed polymer was stoichiometrically combined with Ru(bda)(DMSO)(4-picoline) in dry methanol (10-15 mL) and stirred overnight under N2 atmosphere to obtain a coordination copolymer; a portion of the reaction volume was removed and added to dry methanol to a final concentration of 0.25 mM for immobilization; the immobilized solution was stored in the dark at room temperature to form a reddish-brown solution (polymer grafted with catalyst).
[0032] Preferably, in step S5, the preparation of the photosensitizer (RuPSL) includes the following steps: The mixture of [Ru(Cl)2(py)2] (1.56 mmol) and 4,4'-heptadecyl-2,2'-bipyridine (1.54 mmol) in a 1:1:1 mixture of ethanol:water:chloroform (60 mL) was degassed by bubbling with N2 for 15 min, and then heated at 110 °C for 2 days. After cooling to room temperature, the orange-red fraction was extracted and separated. The solvent was removed by air separation, and the red compound was extracted with chloroform to obtain the desired compound RuPSL.
[0033] This invention also discloses the application of the above-mentioned polymer electrolyte material photoanode in photoelectrocatalysis, including the following steps: A three-electrode system was constructed using a polymer electrolyte material photoanode as the working electrode to carry out an electrocatalytic reaction in an electrolyte solution, thereby releasing oxygen.
[0034] Preferably, the electrolyte solution is a neutral solution; the concentration of the electrolyte solution is 0.5 M.
[0035] Preferably, the neutral solution is a phosphate buffer solution with 0.5 M sodium perchlorate added.
[0036] The chemical structural formula of the photosensitizer is as follows: .
[0037] The chemical formula of the catalyst is: .
[0038] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0039] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0040] Example 1 A method for preparing a polymer electrolyte material photoanode includes the following steps: In this embodiment, the catalyst and photosensitizer self-assemble through non-molecular interactions. The molecular ratio of photosensitizer RuPSL to catalyst Ru-bda in the photoelectroanode of the electrolyte material is 1, and both photosensitizer RuPSL and catalyst Ru-bda are powder samples. The catalyst monomer synthesis section was as follows: 488 mg of 2,2'-bipyridine-6,6'-dicarboxylic acid, 968 mg of Ru(DMSO)4Cl2, and 1.6 mL of NEt3 were added to 80 mL of methanol and refluxed with N2 for 4 h to obtain Ru(bda)(DMSO)2; a mixture of 4-pyridine (93 mg) and Ru(bda)(DMSO)2 (500 mg) in methanol (40 mL) was degassed with N2 and refluxed for 1 h, and the product was purified by silica gel column chromatography using dichloromethane-methanol (1:1, v:v) as the eluent. The copolymer synthesis process involved dissolving 45 mg of pyridin-4-yl 2-methylpropionic acid, 34 mg of {[(2-methyl-1-oxoylide-2-enyl)oxy]methyl}phosphonate diethyl ester, and 32 mg of decyl 2-methylpropionic acid in 7 mL of anhydrous and oxygen-free THF. The mixture was subjected to three freeze-pump-thaw cycles under a nitrogen atmosphere to remove O2 from the solvent. The mixture was then heated to 70 °C and refluxed for 48 h. Heating was stopped, and the mixture was allowed to cool to room temperature. The crude product in tetrahydrofuran was concentrated to 1 mL, and then 50 mL of n-hexane was added to precipitate the copolymer. The solid was filtered and washed with n-hexane to remove unreacted monomers. The product was separated and dried under high vacuum to obtain a white solid. The unhydrolyzed polymer was dissolved in 2 mL of dry DCM, and excess trimethylbromosilane was added at 0 °C under a N2 atmosphere. The reaction mixture was then transferred from 0... The mixture was heated to room temperature and stirred overnight. Then, excess methanol was added to precipitate the copolymer. The solid was filtered and washed with methanol. The product was separated and dried under high vacuum to obtain a pale yellow solid. The coordination reaction of the hydrolyzed polymer and the catalyst was carried out as follows: 10 mg of the corresponding dry hydrolyzed polymer was stoichiometrically combined with 32 mg of Ru(bda)(DMSO)(4-picoline) in 8 mL of dry methanol and stirred overnight under N2 atmosphere to obtain a coordination copolymer. After removing part of the reaction volume, it was added to dry methanol to a final concentration of 0.25 mM for immobilization. The immobilized solution was stored in the dark at room temperature to form a reddish-brown solution. The photosensitizer was synthesized as follows: a mixture of [Ru(Cl)2(py)2] (1.56 mmol) and 4,4'-heptadecyl-2,2'-bipyridine (1.54 mmol) in a 1:1:1 mixture of ethanol:water:chloroform (60 mL) was degassed by bubbling with N2 for 15 min, then heated at 110 °C for 2 days. After cooling to room temperature, the orange-red fraction was extracted and separated. The solvent was removed by air separation, and the red compound was extracted with chloroform to obtain the desired compound RuPSL. The photosensitizer solution was obtained by mixing the photosensitizer and methanol at a concentration of 5 mg / mL. 5 mg of the grafted catalyst polymer was dissolved in 5 mL of methanol to obtain a mixed solution; a core-shell structured electrode was coated on the substrate and then immersed in the mixed solution to obtain the surface-anchored catalyst assembled electrode FTO|SnO2 / TiO2|-polymer-Rubda (electrode 2); the surface-anchored catalyst assembled electrode was placed in a photosensitizer solution to obtain the polymer electrolyte material photoanode FTO|SnO2 / TiO2|-polymer-Rubda-PuPSL (electrode 1).
[0041] Using the polymer electrolyte material photoanode prepared in Example 1 as the working electrode, platinum wire as the counter electrode, and saturated silver chloride electrode as the reference electrode, a three-electrode system was constructed, and photoelectrocatalytic reaction was carried out in 1 M phosphate buffer solution (electrolyte solution, pH 7).
[0042] Example 2 A method for preparing a polymer electrolyte material photoanode includes the following steps: The catalyst monomer synthesis section was as follows: 488 mg of 2,2'-bipyridine-6,6'-dicarboxylic acid, 968 mg of Ru(DMSO)4Cl2, and 1.6 mL of NEt3 were added to 80 mL of methanol and refluxed with N2 for 4 h to obtain Ru(bda)(DMSO)2; a mixture of 4-pyridine (93 mg) and Ru(bda)(DMSO)2 (500 mg) in methanol (40 mL) was degassed with N2 and refluxed for 1 h, and the product was purified by silica gel column chromatography using dichloromethane-methanol (1:1, v:v) as the eluent. The copolymer synthesis process involved dissolving 50 mg of pyridin-4-yl 2-methylpropionic acid, 30 mg of {[(2-methyl-1-oxoylide-2-enyl)oxy]methyl}phosphonate diethyl ester, and 40 mg of decyl 2-methylpropionic acid in 15 mL of anhydrous and oxygen-free THF. The mixture was subjected to three freeze-pump-thaw cycles under a nitrogen atmosphere to remove O2 from the solvent. The mixture was then heated to 90 °C and refluxed for 36 h. Heating was stopped, and the mixture was allowed to cool to room temperature. The crude product in tetrahydrofuran was concentrated to 2 mL, and then 80 mL of n-hexane was added to precipitate the copolymer. The solid was filtered and washed with n-hexane to remove unreacted monomers. The product was separated and dried under high vacuum to obtain a white solid. The unhydrolyzed polymer was dissolved in 20 mL of dry DCM, and excess trimethylbromosilane was added at 0 °C under a N2 atmosphere. The reaction mixture was then transferred from 0... The mixture was heated to room temperature and stirred overnight. Then, excess methanol was added to precipitate the copolymer. The solid was filtered and washed with methanol. The product was separated and dried under high vacuum to obtain a pale yellow solid (hydrolyzed polymer). The coordination reaction of the hydrolyzed polymer and the catalyst was carried out as follows: 20 mg of the corresponding dry hydrolyzed polymer was stoichiometrically combined with 50 mg of Ru(bda)(DMSO)(4-picoline) in 5 mL of dry methanol and stirred overnight under N2 atmosphere to obtain a coordination copolymer. After removing part of the reaction volume, it was added to dry methanol to a final concentration of 0.25 mM for immobilization. The immobilized solution was stored in the dark at room temperature to form a reddish-brown solution. The photosensitizer was synthesized as follows: a mixture of [Ru(Cl)2(py)2] (1.56 mmol) and 4,4'-heptadecyl-2,2'-bipyridine (1.54 mmol) in a 1:1:1 mixture of ethanol:water:chloroform (60 mL) was degassed by bubbling with N2 for 15 min, then heated at 120 °C for 3 days. After cooling to room temperature, the orange-red fraction was extracted and separated. The solvent was removed by air separation, and the red compound was extracted with chloroform to obtain the desired compound RuPSL. The photosensitizer solution was obtained by mixing the photosensitizer and methanol at a concentration of 8 mg / mL. 5 mg of the polymer grafted with the catalyst was dissolved in 5 mL of methanol to obtain a mixed solution; a core-shell structured electrode was coated on the substrate and then immersed in the mixed solution to obtain an assembled electrode with a surface-anchored catalyst; the assembled electrode with the surface-anchored catalyst was placed in a photosensitizer solution to obtain a polymer electrolyte material photoanode.
[0043] Example 3 A method for preparing a polymer electrolyte material photoanode includes the following steps: The catalyst monomer synthesis section was as follows: 488 mg of 2,2'-bipyridine-6,6'-dicarboxylic acid, 968 mg of Ru(DMSO)4Cl2, and 1.6 mL of NEt3 were added to 80 mL of methanol and refluxed with N2 for 4 h to obtain Ru(bda)(DMSO)2; a mixture of 4-pyridine (93 mg) and Ru(bda)(DMSO)2 (500 mg) in methanol (40 mL) was degassed with N2 and refluxed for 1 h, and the product was purified by silica gel column chromatography using dichloromethane-methanol (1:1, v:v) as the eluent. The copolymer synthesis process involved dissolving 40 mg of pyridin-4-yl 2-methylpropionic acid, 10 mg of {[(2-methyl-1-oxoylide-2-enyl)oxy]methyl}phosphonate diethyl ester, and 30 mg of decyl 2-methylpropionic acid in 10 mL of anhydrous and oxygen-free THF. The mixture was subjected to three freeze-pump-thaw cycles under a nitrogen atmosphere to remove O2 from the solvent. The mixture was then heated to 90 °C and refluxed for 36 h. Heating was stopped, and the mixture was allowed to cool to room temperature. The crude product in tetrahydrofuran was concentrated to 2 mL, and then 80 mL of n-hexane was added to precipitate the copolymer. The solid was filtered and washed with n-hexane to remove unreacted monomers. The product was separated and dried under high vacuum to obtain a white solid. The unhydrolyzed polymer was dissolved in 20 mL of dry DCM, and excess trimethylbromosilane was added at 0 °C under a N2 atmosphere. The reaction mixture was then transferred from 0... The mixture was heated to room temperature and stirred overnight. Then, excess methanol was added to precipitate the copolymer. The solid was filtered and washed with methanol. The product was separated and dried under high vacuum to obtain a pale yellow solid (hydrolyzed polymer). The coordination reaction of the hydrolyzed polymer and the catalyst was carried out as follows: 20 mg of the corresponding dry hydrolyzed polymer was stoichiometrically combined with 50 mg of Ru(bda)(DMSO)(4-picoline) in 7 mL of dry acetonitrile and stirred overnight under N2 atmosphere to obtain a coordination copolymer. After removing part of the reaction volume, it was added to dry methanol to a final concentration of 0.25 mM for immobilization. The immobilized solution was stored in the dark at room temperature to form a reddish-brown solution. The photosensitizer was synthesized as follows: a mixture of [Ru(Cl)2(py)2] (1.56 mmol) and 4,4'-heptadecyl-2,2'-bipyridine (1.54 mmol) in a 1:1:1 mixture of ethanol:water:chloroform (60 mL) was degassed by bubbling with N2 for 15 min, then heated at 120 °C for 3 days. After cooling to room temperature, the orange-red fraction was extracted and separated. The solvent was removed by air separation, and the red compound was extracted with chloroform to obtain the desired compound RuPSL. The photosensitizer solution was obtained by mixing the photosensitizer and methanol at a concentration of 8 mg / mL. 5 mg of the polymer grafted with the catalyst was dissolved in 5 mL of methanol to obtain a mixed solution; a core-shell structured electrode was coated on the substrate and then immersed in the mixed solution to obtain an assembled electrode with a surface-anchored catalyst; the assembled electrode with the surface-anchored catalyst was placed in a photosensitizer solution to obtain a polymer electrolyte material photoanode.
[0044] Comparative Example Using pretreated FTO|TiO2 as a control group, photoelectrocatalysis was performed under the same conditions.
[0045] The potentials of all the above electrodes are calibrated to the reversible hydrogen electrode (RHE).
[0046] Figure 1 The above are the 1H NMR spectra of the Ru(bda)(DMSO)(4-picoline) catalyst and RuPSL photosensitizer prepared in Example 1 of this invention, where a represents Ru(bda)(DMSO)(4-picoline). 1 H NMR (400MHz, CD3OD): δ 8.5 (m, 2H), 8.1 (t, 4H), 7.7 (d, 2H), 7.1 (d, 2H), 2.9 (s, 6H), 2.3 (s, 3H)., b is RuPSL, 1 ¹H NMR (400 MHz, CD₃OD): δ 8.71–8.69 (d, 4H), 8.62 (d, 2H), 8.14–8.10 (t, 4H), 7.82–7.81 (m, 4H), 7.64–7.62 (d, 2H), 7.51–7.46 (t, 4H), 7.35–7.34 (dd, 2H), 2.87–2.83 (t, 4H), 1.77–1.70 (q, 4H), 1.40–1.25 (m, 56H), 0.91–0.88 (t, 6H). This indicates that Ru(bda)(DMSO)(4-picoline) was successfully synthesized.
[0047] Figure 2 The infrared spectrum of the copolymer prepared in Example 1 of this invention shows that the polymer scaffold was successfully synthesized. The pyridine ring exhibits a skeletal stretching vibration band of 1600 cm⁻¹. -1 The characteristic infrared absorption peak of the PO bond is at 1150 cm⁻¹. -1 .
[0048] Figure 3The image shows the ultraviolet absorption spectrum of the photoanode of the polymer electrolyte material photoanode prepared in Example 1 of this invention. It can be seen that when the assembled electrode with the surface anchored catalyst is placed in the methanol solution of the photosensitizer, the absorbance of the photosensitizer / catalyst assembled electrode at 450 nm increases, proving that the photosensitizer / catalyst assembled electrode was successfully prepared by self-assembly.
[0049] Figure 4 The graph shows the photoelectrocatalytic performance of the polymer electrolyte material photoanode prepared in Example 1 of this invention. It can be seen that the SnO2 / TiO2 core / shell structure exhibits better local charge separation, because the conduction band potential difference between the oxides creates an energy barrier. After 90 s of illumination, the photocurrent density of the FTO|SnO2 / TiO2|-polymer-Rubda-PuPSL (electrode 1) assembly is 0.28 mA / cm². 2 .
[0050] Figure 5 The image shows the long-term photocurrent test results and the oxygen evolution rate in the photoelectrocatalytic water splitting reaction of the polymer electrolyte material photoanode prepared in Example 1 of this invention. It can be seen that after continuous illumination for 3000 s, the photocurrent density of FTO|SnO2 / TiO2|-polymer-Rubda-PuPSL is 0.1 mA / cm². 2 The current retention rate was 33%, and 0.14 μmol of O2 was generated.
[0051] Figure 6 The graph shows the photoelectric conversion efficiency of the polymer electrolyte material photoanode prepared in Example 1 of this invention. It can be seen that the efficiency of FTO|SnO2 / TiO2|-polymer-Rubda-PuPSL in generating photocurrent at a wavelength of 450 nm reached 13.7%, which is one of the high values of organic photosensitizers in the water oxidation of DSPECs.
[0052] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing a polymer electrolyte material photoanode, characterized in that, Includes the following steps: The copolymer was subjected to a hydrolysis reaction to obtain the hydrolyzed polymer; the hydrolyzed polymer and the catalyst were then subjected to a coordination reaction to obtain the polymer grafted with the catalyst. The polymer grafted with the catalyst was dissolved in a solvent to obtain a mixed solution; After coating a core-shell structured electrode onto a substrate, the electrode is immersed in a mixed solution to obtain an assembled electrode with a surface-anchored catalyst. By placing the assembled electrode with the surface-anchored catalyst in a photosensitizer solution, a polymer electrolyte material photoanode is obtained. The copolymer is prepared by: 2-Methylpropion-2-enoic acid pyridin-4-yl ester, {[(2-methyl-1-oxylidenepropion-2-enyl)oxy]methyl}phosphonate diethyl ester, and 2-methylpropion-2-enoic acid decyl ester were dissolved in THF and subjected to a freeze-pump-thaw cycle under a nitrogen atmosphere, followed by reflux to obtain a mixture. The mixture was cooled and concentrated to obtain a crude product. A hexane copolymer was added to the crude product to react and obtain a copolymer. The ratio of 2-methylpropion-2-enoic acid pyridin-4-yl ester, {[(2-methyl-1-oxylidenepropion-2-enyl)oxy]methyl}phosphonate diethyl ester, 2-methylpropion-2-enoic acid decyl ester, and THF was (40~50) mg: (10~30) mg: (30~40) mg: (7~15) mL. The freeze-pump-thaw cycle was performed three times. The reflux was performed by heating to 70~90°C. Reflux at ℃ for 36-48 h; the ratio of the crude product to the n-hexane copolymer is (1-2) mL: (50-80) mL; The catalyst is prepared by: 2,2'-Bipyridine-6,6'-dicarboxylic acid, Ru(DMSO)4Cl2, and NEt3 were added to methanol and refluxed under a N2 atmosphere to obtain Ru(bda)(DMSO)2. 4-Pyridine, Ru(bda)(DMSO)2, and methanol were mixed, degassed under a N2 atmosphere, and refluxed. After elution and purification, Ru(bda)(DMSO)(4-picoline) catalyst was obtained. The molar ratio of 2,2'-bipyridine-6,6'-dicarboxylic acid, Ru(DMSO)4Cl2, NEt3, and methanol was 488 mg:968 mg:1.6 mL:80 mL. Reflux under a N2 atmosphere for 4 h yielded Ru(bda)(DMSO)2. The molar ratio of 4-pyridine, Ru(bda)(DMSO)2, and methanol was 93 mg:500 mg:40 mL. The reflux time for obtaining the Ru(bda)(DMSO)(4-picoline) catalyst was 1 h; the eluent used for elution was a mixture of dichloromethane and methanol in a volume ratio of 1:
1. The photosensitizer is prepared by: [Ru(Cl)2(py)2] and 4,4'-heptadecyl-2,2'-bipyridine were dissolved in a mixed solvent, followed by degassing with N2 bubbling and heating to obtain the product. The product was then extracted and the solvent was removed to obtain a photosensitizer. The volume ratio of [Ru(Cl)2(py)2], 4,4'-heptadecyl-2,2'-bipyridine, and the mixed solvent was 1.56 mmol:1.54 mmol:60 mL. The mixed solvent was a mixture of ethanol, water, and chloroform in a volume ratio of 1:1:
1. The heating temperature was 110-120 °C, and the heating time was 2-3 days.
2. The method for preparing a polymer electrolyte material photoanode according to claim 1, characterized in that, The chemical structural formula of the hydrolyzed polymer is shown below: ; Where: R is C 10 H 21 Long alkyl chain.
3. The method for preparing a polymer electrolyte material photoanode according to claim 1, characterized in that, The specific steps for the hydrolysis reaction of the copolymer are as follows: The copolymer was dissolved in DCM, and then an excess of trimethylbromosilane was added under N2 atmosphere to react and obtain a reaction mixture. The reaction mixture was heated and stirred, and then an excess of methanol was added to obtain the precipitated copolymer. The precipitated copolymer was washed and dried sequentially to obtain the hydrolyzed polymer. The ratio of the copolymer to DCM is (30~50) mg : (2~20) mL; The ratio of the copolymer, trimethylbromosilane, and methanol is (30~50) mg: (1-3) mL: (1-3) mL; The temperature at which excess trimethylbromosilane is added is 0 °C; The heating process involves heating from 0 °C to room temperature; the stirring time is 12 h.
4. The method for preparing a polymer electrolyte material photoanode according to claim 1, characterized in that, The specific steps for the coordination reaction between the hydrolyzed polymer and the catalyst are as follows: The hydrolyzed polymer and catalyst were stoichiometrically combined in methanol and a coordination reaction was carried out under N2 atmosphere to obtain a polymer grafted with the catalyst. The ratio of the hydrolyzed polymer to the catalyst is (10~20) mg: (32~50) mg; The ratio of polymer to solvent in the grafted catalyst is (5~10) mg: (5~8) mL; The solvent is methanol or acetonitrile.
5. The method for preparing a polymer electrolyte material photoanode according to claim 1, characterized in that, The photosensitizer solution is obtained by mixing a photosensitizer and methanol; the concentration of the photosensitizer solution is 5~8 mg / mL.
6. A polymer electrolyte material photoanode, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 5.
7. The application of the polymer electrolyte material photoanode according to claim 6 in photoelectrocatalysis, characterized in that, Includes the following steps: Using photoelectrocatalysis as the working electrode, a three-electrode system was constructed. Electrocatalytic reactions were carried out in the electrolyte solution of the three-electrode system to release oxygen.
8. The application of the polymer electrolyte material photoanode according to claim 7 in photoelectrocatalysis, characterized in that, The electrolyte solution is a neutral solution; the concentration of the electrolyte solution is 0.5 M. The neutral solution was prepared by adding 0.5 M sodium perchlorate to a phosphate buffer solution.
Citation Information
Patent Citations
Preparation method of porphyrin sensitized SnO2 bionic photoanode with high oxidizability
CN107301920A
Dye-sensitized solar cell based on titanium dioxide core-shell particle photoanode
CN109003822A
